2014
DOI: 10.1071/sr14016
|View full text |Cite
|
Sign up to set email alerts
|

Testing a new method for sequential silicon extraction on soils of a temperate–humid climate

Abstract: The importance of silicon (Si) compounds in agriculture and geochemical cycles has received increasing attention over the last decade; however, quantitative data on non-crystalline pedogenic Si phases in soils are still rare. Recently, the authors developed a method for sequential Si extraction from soils, in order to improve the quantification of different Si compounds in soils. The method has been tested on samples of known composition. Here, the method is applied for the first time to complete soil profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…This hypothesis is further supported by SEM microscopy, where only a few (wet shrub tundra) to no diatoms and/or phytoliths (moist shrub-, dry shrub-and lichen tundra) were observed in the mineral layer of all the shrub tundra classes. Other studies, applying various techniques to determine ASi storage in soil, support this shift from biogenic Si to pedogenic Si fractions with depth (Saccone et al 2007;Sommer et al 2013;Georgiadis et al 2014;Blecker et al 2006;Cornelis et al 2014). However, some of the ASi in the mineral layer may be of biogenic origin since ASi can be translocated downward the soil profile (Fishkis et al 2010) through the process of e.g.…”
Section: Partitioning Of Soc and Asi Storage In Arctic Landscapesmentioning
confidence: 86%
“…This hypothesis is further supported by SEM microscopy, where only a few (wet shrub tundra) to no diatoms and/or phytoliths (moist shrub-, dry shrub-and lichen tundra) were observed in the mineral layer of all the shrub tundra classes. Other studies, applying various techniques to determine ASi storage in soil, support this shift from biogenic Si to pedogenic Si fractions with depth (Saccone et al 2007;Sommer et al 2013;Georgiadis et al 2014;Blecker et al 2006;Cornelis et al 2014). However, some of the ASi in the mineral layer may be of biogenic origin since ASi can be translocated downward the soil profile (Fishkis et al 2010) through the process of e.g.…”
Section: Partitioning Of Soc and Asi Storage In Arctic Landscapesmentioning
confidence: 86%
“…Although still present, diatoms and phytoliths appeared more scarce and fragmented in deeper mineral horizons. Other studies, applying different techniques to quantify ASi, support this shift from a dominance of biologically formed ASi in the top (organic) soil toward a dominance of pedogenic ASi with depth [ Barão et al ., , ; Georgiadis et al ., ; Sommer et al ., ; White et al ., ].…”
Section: Discussionmentioning
confidence: 97%
“…When compared to other methods [ Barão et al ., , ; Meunier et al ., ], the Na 2 CO 3 extraction method has proven to be reliable for determination of ASi of biogenic origin in fresh vegetation material and top organic soils. In deeper mineral soils, pedogenic fractions and partial dissolution of clays may contribute significantly to the ASi pool extracted [ Barão et al ., , ; Georgiadis et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Niederbudde and Kussmaul () reported a ‘degree of chloritization' of 48% for the clay fraction of an E horizon (pH 3.8) and of 39% for the clay fraction of an Ah horizon (pH 4.5) in a forested Luvisol developed from loess. Georgiadis et al () found the largest proportions of HIMs in acidic organic and mineral topsoil horizons of Podzols developed from sandstone in the Black Forest (Germany). However, their occurrence is not necessarily the consequence of their recent formation, as they might be remnants of earlier stages of soil formation ( Blum , ).…”
Section: Formation and Formation Conditions Of Hims In Soilmentioning
confidence: 99%